Join the IDNLearn.com community and start getting the answers you need today. Our experts provide timely, comprehensive responses to ensure you have the information you need.
Sagot :
Sure, let's solve the quadratic equation [tex]\((x - 8)^2 - 13(x - 8) + 30 = 0\)[/tex] using the substitution method step-by-step.
1. Substitution:
Start by substituting [tex]\( u = x - 8 \)[/tex]. This substitution simplifies our equation into a more standard quadratic form.
[tex]\[ (x - 8)^2 - 13(x - 8) + 30 = u^2 - 13u + 30 = 0 \][/tex]
2. Quadratic Equation:
Now we need to solve the quadratic equation in terms of [tex]\(u\)[/tex]:
[tex]\[ u^2 - 13u + 30 = 0 \][/tex]
3. Quadratic Formula:
The general form of the quadratic equation is [tex]\( au^2 + bu + c = 0 \)[/tex]. Here, [tex]\(a = 1\)[/tex], [tex]\(b = -13\)[/tex], and [tex]\(c = 30\)[/tex]. Using the quadratic formula:
[tex]\[ u = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
Substituting the values:
[tex]\[ u = \frac{{-(-13) \pm \sqrt{{(-13)^2 - 4 \cdot 1 \cdot 30}}}}{2 \cdot 1} \][/tex]
Simplifying the discriminant:
[tex]\[ u = \frac{{13 \pm \sqrt{{169 - 120}}}}{2} \][/tex]
[tex]\[ u = \frac{{13 \pm \sqrt{49}}}{2} \][/tex]
[tex]\[ u = \frac{{13 \pm 7}}{2} \][/tex]
4. Solving for [tex]\(u\)[/tex]:
This gives us two values for [tex]\(u\)[/tex]:
[tex]\[ u = \frac{{13 + 7}}{2} = \frac{20}{2} = 10 \][/tex]
[tex]\[ u = \frac{{13 - 7}}{2} = \frac{6}{2} = 3 \][/tex]
5. Back Substitution:
We revert back to the original variable [tex]\(x\)[/tex], using the substitution [tex]\( u = x - 8 \)[/tex]:
[tex]\[ u = 10 \Rightarrow x - 8 = 10 \Rightarrow x = 18 \][/tex]
[tex]\[ u = 3 \Rightarrow x - 8 = 3 \Rightarrow x = 11 \][/tex]
6. Solutions:
Therefore, the solutions to the equation [tex]\((x - 8)^2 - 13(x - 8) + 30 = 0\)[/tex] are:
[tex]\[ x = 11 \quad \text{and} \quad x = 18 \][/tex]
So, the correct option is:
[tex]\[ \boxed{x = 11 \text{ and } x = 18} \][/tex]
1. Substitution:
Start by substituting [tex]\( u = x - 8 \)[/tex]. This substitution simplifies our equation into a more standard quadratic form.
[tex]\[ (x - 8)^2 - 13(x - 8) + 30 = u^2 - 13u + 30 = 0 \][/tex]
2. Quadratic Equation:
Now we need to solve the quadratic equation in terms of [tex]\(u\)[/tex]:
[tex]\[ u^2 - 13u + 30 = 0 \][/tex]
3. Quadratic Formula:
The general form of the quadratic equation is [tex]\( au^2 + bu + c = 0 \)[/tex]. Here, [tex]\(a = 1\)[/tex], [tex]\(b = -13\)[/tex], and [tex]\(c = 30\)[/tex]. Using the quadratic formula:
[tex]\[ u = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
Substituting the values:
[tex]\[ u = \frac{{-(-13) \pm \sqrt{{(-13)^2 - 4 \cdot 1 \cdot 30}}}}{2 \cdot 1} \][/tex]
Simplifying the discriminant:
[tex]\[ u = \frac{{13 \pm \sqrt{{169 - 120}}}}{2} \][/tex]
[tex]\[ u = \frac{{13 \pm \sqrt{49}}}{2} \][/tex]
[tex]\[ u = \frac{{13 \pm 7}}{2} \][/tex]
4. Solving for [tex]\(u\)[/tex]:
This gives us two values for [tex]\(u\)[/tex]:
[tex]\[ u = \frac{{13 + 7}}{2} = \frac{20}{2} = 10 \][/tex]
[tex]\[ u = \frac{{13 - 7}}{2} = \frac{6}{2} = 3 \][/tex]
5. Back Substitution:
We revert back to the original variable [tex]\(x\)[/tex], using the substitution [tex]\( u = x - 8 \)[/tex]:
[tex]\[ u = 10 \Rightarrow x - 8 = 10 \Rightarrow x = 18 \][/tex]
[tex]\[ u = 3 \Rightarrow x - 8 = 3 \Rightarrow x = 11 \][/tex]
6. Solutions:
Therefore, the solutions to the equation [tex]\((x - 8)^2 - 13(x - 8) + 30 = 0\)[/tex] are:
[tex]\[ x = 11 \quad \text{and} \quad x = 18 \][/tex]
So, the correct option is:
[tex]\[ \boxed{x = 11 \text{ and } x = 18} \][/tex]
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. For clear and precise answers, choose IDNLearn.com. Thanks for stopping by, and come back soon for more valuable insights.